Avaliação tomográfica dos incisivos inferiores após expansão do arco com o uso do aparelho transforce® - Peron-Berbert, Daniele Fernanda (2012)
This study analyzed, by cone-beam computed tomography, the thickness of the buccal bone plate of mandibular incisors (mandibular right and left central and lateral incisors) and its correlation with the inclination of mandibular central incisors (mandibular right and left central incisors) before (T1) and after (T2) mandibular arch transverse expansion using the Transforce® appliance. The sample was selected from 50 patients from the Master clinic in Orthodontics at University of São Paulo City and included nine patients of both genders selected according to the criteria of inclusion. The method error was evaluated by intra-examiner agreement (ICC), Dahlberg method error and paired t test, which did not reveal statistical differences between the measurements. Correlation between inclination and the buccal bone plate was analyzed by the paired t test. The results evidenced statistically significant reduction of the buccal bone plate only for the mandibular left central incisor (p 0.001) and lateral incisor (p 0.016) in the medium level. It was observed correlation was found between inclination and thickness of buccal bone plate by the Pearson test the tooth 41 only (p 0.001). It was concluded that the Transforce® appliance is effective for correction of moderate crowding in short treatment period.